Daya Tahan Panas Pada Sapi Peranakan Simmental, Peranakan Ongole Dan Sapi Pesisir. - S. Nawaan (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2006)
This research was conducted to study heat tolerance (HT) of three breed cattle of Simmental Crossbred, Ongole Crossbred and Pesisir Cattle. The animals were reared semi extensively by farmers in low land area of Pariaman, Pesisir districts and Padang city of West Sumatra. Sixty-four cows consisting of 14 Simental crossbred, 25 Ongole crossbred and 25 Pesisir bred was used in this study. Each animal was measured for skin and rectum temperature, rate of respiration and heart. Body temperature and heat tolerance coefficient (HTC) were then calculated by using the measured data. Results showed that Pesisir bred was found the highest HTC (95.86), followed by Simental crossbred (92.94) and Ongole crossed bred (87.54).